Identifikasi Boraks dan Formalin pada Jajanan Mahasiswa di Sekitar Kampus Universitas Negeri Makassar - Sahrani U; Hasri Hasri; Nur Indah Sari (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Food safety is an important aspect in maintaining public health, particularly in street foods that are widely consumed by university students. However, the misuse of hazardous food additives such as borax is still found in various food products. This study aims to identify the presence of borax in student snacks sold around the campus of Universitas Negeri Makassar. This research employed a descriptive method with both qualitative and quantitative approaches. The samples consisted of meatballs (bakso), dim sum, noodles, and siomay, selected using a purposive sampling technique. The qualitative test was conducted using turmeric paper, while the quantitative test was carried out using a titration method with 0.1 N H₂SO₄ solution and methyl red indicator. The results showed that in the qualitative test, the noodle sample gave a positive result, indicated by a color change of the turmeric paper to yellowish-brown. Meanwhile, the quantitative test showed that the meatball sample had an average titrant volume of 2.67 mL, which was higher than the borax standard of 2.00 mL, indicating the presence of borax. The dim sum and siomay samples showed negative results for borax content. This study indicates that there is still a potential use of borax in student snacks around the campus environment; therefore, continuous food safety monitoring is required.